Civil society in the Middle East. - Norton, Augustus R. (Social, economic, and political studies of the Middle East ;, 1996)
Civil Society in the Middle East is a project of the Department of Politics and the Koverkian Center for Near Eastern Studies, New York University. Project director is Augustus Richard Norton (Boston University). While there is wide disagreement about the outcome among those who follow events in the Middle East, there is little doubt that the regimes in the region are under increasing pressure from their citizens. In rich and poor states alike, incipient movements of men and women are demanding a voice in politics. Recent political developments in Jordan, Yemen, Lebanon, even the future state of Palestine, clearly show the vitality and dynamism of civil society, the melange of associations, clubs, guilds, syndicates, federations, unions, parties and groups which provide a buffer between state and citizen and which are now so clearly at the forefront of political liberalization in the region. Civil Society in the Middle East, a two-volume set of papers providing an unusually detailed and rich assessment of contemporary politics within the Middle East, and in this sense alone, quite literally peerless, is the result of a project of the Department of Politics and the Kevorkian Center for Near Eastern Studies at New York University. Volume I contains contributions by Augustus Richard Norton, Raymond A. Hinnebusch, Laurie Brand, Muhammad Muslih, Mustafa Kamil al-Sayyid, Ghanim al Najjar and Neil Hicks, Eva Bellin, Jill Crystal, Saad al-Din Ibrahim, and Alan Richards.